2009
DOI: 10.1016/j.ijgo.2009.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal mortality audit: Counting, accountability, and overcoming challenges in scaling up in low- and middle-income countries

Abstract: The effect of perinatal audit depends on the ability to close the audit loop; without effectively implementing the solutions to the problems identified, audit alone cannot improve quality of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
157
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(163 citation statements)
references
References 35 publications
2
157
0
4
Order By: Relevance
“…Improvement of staff training and attention to quality of care is key and needs to be linked to some form of institutional assessment of staff quality and training in relation to birth outcomes and perinatal audits. [100][101][102] Such assessment is particularly important because excess maternal morbidity is associated with inappropriate interventions and operative deliveries in facilities. 103 In settings with substantial shortage of skilled attendants, training of midwives and linkage of health facilities to trained traditional birth attendants could provide a short-term solution, but should not detract from long-term investments and approaches to care.…”
Section: N S E C T I C I D E -T R E a T E D B E D N E T S O R I N Tmentioning
confidence: 99%
“…Improvement of staff training and attention to quality of care is key and needs to be linked to some form of institutional assessment of staff quality and training in relation to birth outcomes and perinatal audits. [100][101][102] Such assessment is particularly important because excess maternal morbidity is associated with inappropriate interventions and operative deliveries in facilities. 103 In settings with substantial shortage of skilled attendants, training of midwives and linkage of health facilities to trained traditional birth attendants could provide a short-term solution, but should not detract from long-term investments and approaches to care.…”
Section: N S E C T I C I D E -T R E a T E D B E D N E T S O R I N Tmentioning
confidence: 99%
“…Although few studies have been done in lowincome and middle-income countries, reported eff ect sizes range from small to moderate for improved provider prac tices [61][62][63] and are large for drug management 64 and perinatal and intrapartum mortality. 64,65 Increased supervision is another strategy used to improve health-worker performance in low-income and middle-income countries and has moderate-to-large eff ects. 64 This evidence is diffi cult to summarise, however, because of the absence of a standard defi nition of the supervisory function and variation in implementation and outcomes studied.…”
Section: Improving Continuity Of Carementioning
confidence: 99%
“…Encontramos que el SNVEPN tiene un subregistro de defunciones de 53%, menor al SHV; se demuestra al igual que otros estudios, que la vigilancia epidemiológica es más confiable que otros sistemas de información en el registro de muertes neonatales (18)(19)(20)(21)(22) . La notificación obligatoria de defunciones fetales y neonatales se dispuso en Perú hace tres años y aún se continúa incorporando establecimientos de salud del primer nivel de atención y establecimientos de salud procedente de EsSalud y Fuerzas Policiales, por lo que se espera mejorar progresivamente la cobertura de notificación.…”
Section: Discussionunclassified